2012
DOI: 10.1371/journal.pone.0049029
|View full text |Cite
|
Sign up to set email alerts
|

Wiki-Pi: A Web-Server of Annotated Human Protein-Protein Interactions to Aid in Discovery of Protein Function

Abstract: Protein-protein interactions (PPIs) are the basis of biological functions. Knowledge of the interactions of a protein can help understand its molecular function and its association with different biological processes and pathways. Several publicly available databases provide comprehensive information about individual proteins, such as their sequence, structure, and function. There also exist databases that are built exclusively to provide PPIs by curating them from published literature. The information provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 39 publications
1
60
0
1
Order By: Relevance
“…We then identified eight TFs that are associated with these distal z-HPRs (Table 2). Of note, among these identified TFs, four were previously reported to physically interact [TAL1-LIM domain only 2 (LMO2), nescient helix loop helix 1 (NHLH1)-LMO2, and TAL1-epididymal sperm binding protein 1 (ELSPB1)], suggesting that they cooperate in regulating H3K27me3 variability and Polycomb activities (44). Importantly, our analysis identified TAL1, a principal regulator of hematopoietic development (39), as a candidate regulator of ProEspecific H3K27me3 variability (Fig.…”
Section: Computational Analysis Identifies Tal1 In Regulating H3k27me3mentioning
confidence: 58%
“…We then identified eight TFs that are associated with these distal z-HPRs (Table 2). Of note, among these identified TFs, four were previously reported to physically interact [TAL1-LIM domain only 2 (LMO2), nescient helix loop helix 1 (NHLH1)-LMO2, and TAL1-epididymal sperm binding protein 1 (ELSPB1)], suggesting that they cooperate in regulating H3K27me3 variability and Polycomb activities (44). Importantly, our analysis identified TAL1, a principal regulator of hematopoietic development (39), as a candidate regulator of ProEspecific H3K27me3 variability (Fig.…”
Section: Computational Analysis Identifies Tal1 In Regulating H3k27me3mentioning
confidence: 58%
“…To study the molecular mechanisms underlying the proliferative phenotype of KPNA1 KO satellite cells, we mined a protein-protein interaction database (Wiki-Pi) [46] based on verified data, and identified 32 KPNA1-interacting proteins. We demonstrated that one of these KPNA1 cargo proteins, p27 (CDKN1B, a cell cycle inhibitor protein), was localized to the cytoplasm in a greater proportion of KPNA1 KO satellite cells than WT although both genotypes showed similar transcript levels.…”
Section: Discussionmentioning
confidence: 99%
“…In order to gain mechanistic insights into the proliferative phenotype of KPNA1 KO satellite cells, we searched for potential cargo proteins of KPNA1 from a protein-protein interaction database (Wiki-Pi) [46]. In humans, 32 proteins are known to interact with KPNA1 and these proteins were grouped into 4 categories by Gene Ontology analysis (Fig.…”
Section: Reduced Nuclear Translocation Of P27 and Increasedmentioning
confidence: 99%
“…When needed, the open source websites "STRING" [89] and Wiki-Pi [90] were used to perform meta-analyses of protein-protein interactions. STRING allows protein interaction networks to be generated via a survey of distinct databases that list known protein interactions from published and manually-curated biochemical studies [89].…”
Section: Meta-analysis Of Mycn Protein Interactantsmentioning
confidence: 99%